An Examination of the Influence of Theory and Individual Theorists on Empirical Research in Microeconomics - Chiappori, Pierre-André; Levitt, Steven D (American Economic Review, 2003)
An Examination of the Influence of Theory and Individual Theorists on Empirical Research in Microeconomics by Pierre-André Chiappori and Steven D. Levitt. Published in volume 93, issue 2, pages 151-155 of American Economic Review, May 2003